(untitled) (Revista Apotheke, 2025)
Interview conducted with Professor Dr. Darcísio Natal Muraro, faculty member in the Pedagogy Program and the Graduate Program in Education at UEL (PPEDUEL), Master’s and Doctorate levels. Professor Darcísio Muraro works in the field of Philosophy of Education and is a Brazilian scholar of the concept of experience and aesthetic experience in John Dewey. In this interview, conducted in person on 02/22/2025 and remotely on 03/17/2025, he shares with us some insights into his research group’s experience, the main themes or concepts studied, the relevance of Dewey’s concept of experience for visual arts students, the relationship between art and philosophy, and the connection between various forms of artistic expression and contemporary democracy.